Implementing Indian Innovations through Trained Extension Functionaries for Improving the Agriculture in Africa and Asia - Shirur, Mahantesh; Sharath, H. N.; Tewari, Goldi; Gummagolmath, K C (Indian Journal of Extension Education, 2022)
Agriculture in India has metamorphosed a lot during the last seven decades from being a subsistence farming to commercial agriculture. The innovations in Indian agriculture have paved the way for seeing agriculture as an agri-business enterprise. The creation of diverse agribusiness opportunities amidst the existing constraints and challenges has reoriented the farming in India. Having seen the positive changes in agriculture due to the agribusiness orientation in India, other countries in Asia and Africa are keen to adopt this approach in their countries. The selected officials representing Government, civil society and private firms from Africa and Asia were trained under Feed the Future India Triangular Training during 2019 on Agribusiness innovations in India and the opportunities for their countries. Following the training, the research study conducted showed that, Indian agribusiness innovations in supply chain management, good agriculture practices and promoting Farmer Producer Companies (FPCs) are perceived as best interventions by the trainees to address the problems of lack of improved technologies for small farmers, unorganized market, lack of institutional resources and lack of agri mechanization in their countries.